Caves - Wood, Jenny (New York : Puffin, 1990)
Explains what caves are, how they are formed, different types, exploration, and the life-forms that inhabit them.
How caves are formed -- Cave systems -- Other types of caves -- Rock formations -- Cave animals -- Cave painting -- Cave dwellers -- True or false -- Exploring caves.
First published in Great Britain : Two-Can, 1990.
Includes index and glossary.
5.5
3-6
3-6
Keywords: Caves -- Juvenile literature; Caves; Caves